PENGARUH SIBLING RIVALRY TERHADAP KETERBUKAAN DIRI PADA TEMAN SEBAYA - Desiana, Salma; Dwi Nurmala, Meilla; Endang Adiningsih, Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the influence  of sibling rivalry on self disclosure to peers. The population in this study is grade VIII students of SMPN 13 Tangerang City. The sampling technique is purposive sampling which produces 76 samples. This study uses a quantitative approach with a correlation method. Normally distributed data with significance values of 0.200 > 0.05. The results of data analysis showed a significant negative influence between sibling rivalry on self disclosure (r = -0.376 and sig 0.001).  The results of the determination coefficient test showed a contribution  of sibling rivalry of 14.2% to self disclosure to peers. Followed by a simple linear regression test, there is a constant value of 88.367 and a regression coefficient value of (-0.239) meaning that if there is no X then Y is 88.367, if there is a 1% increase in sibling rivalry (X) it will decrease self disclosure (Y) by (-0.239). This indicates that the higher the level  of sibling rivalry, the lower the self disclosure experienced by students. The result was that Ha was accepted and Ho was rejected because t counted -3.493 > t table 1.992.